Alcohol reversibly disrupts TNF-α/TACE interactions in the cell membrane - Song, Kejing (BioMed Central, 2005)
BACKGROUND: Alcohol abuse has long been known to adversely affect innate and adaptive immune responses and pre-dispose to infections. One cellular mechanism responsible for this effect is alcohol-induced suppression of TNF-α (TNF) by mononuclear phagocytes. We have previously shown that alcohol in part inhibits TNF-α processing by TNF converting enzyme (TACE) in human monocytes. We hypothesized that the chain length of the alcohol is critical for post-transcriptional suppression of TNF secretion. METHODS: Due to the complex transcriptional and post-transcriptional regulation of TNF in macrophages, to specifically study TNF processing at the cell membrane we performed transient transfections of A549 cells with the TNF cDNA driven by the heterologous CMV promoter. TNF/TACE interactions at the cell surface were assessed using fluorescent resonance energy transfer (FRET) microscopy. RESULTS: The single carbon alcohol, methanol suppressed neither TNF secretion nor FRET efficiency between TNF and TACE. However, 2, 3, and 4 carbon alcohols were potent suppressors of TNF processing and FRET efficiency. The effect of ethanol, a 2-carbon alcohol was reversible. CONCLUSION: These data show that inhibition of TNF-α processing by acute ethanol is a direct affect of ethanol on the cell membrane and is reversible upon cessation or metabolism.